The Problem of Reproduction in Agriculture - Lyudmila A. ZAPOROZHTSEVA1; Yuliya V. TKACHEVA1; Victoria B. MALITSKAYA2; Irina V. KUZNETSOVA1; Natalia A. GORLOVA1 (Communications of International Proceedings, 2020)
The world is now being seriously overhauled, which is seen in economic digitalization and more frequent financial crises growing easily into global financial problems. Reproduction is an urgent matter both for the economic theory and practice, but the approaches towards its understanding have not changed for the last two hundred years. The reproduction process covers distribution and redistribution both on the micro and macro levels. Connection between the development of companies, territories and human capital occurs with the help of reproduction mechanisms. Commercial companies are not only taxation subjects, but also the key agent of distribution and redistribution relations, they form the income of households, take part in investment and social programs, infrastructure development and ensure demand for the products of related industries. Despite the fundamentality of definitions, digitalization promotes development of the balance methods, which undoubtedly covers some aspects of understanding the reproduction category. In modern practice the reproduction category roots in the notion of industry potential, which means that companies’ functioning is a horizontal and vertical basis of the reproduction processes. The article deals with the influence of formalization of distribution and redistribution processes on the micro and macro levels on reproduction of agriculture companies’ potential.
Keywords: Reproduction; Agriculture; Agricultural Companies; State Support